Partners for possibility: experiences of cross-sectoral partnerships designed to improve school leadership in South Africa - Kirori, Maureen Wambui (My University, 2017)
This study explores a partnership model designed by Partners for Possibility (PfP), a South African non-profit organization (NPO) attempting to reform the country’s education system. Through its partnerships, PfP aims to address the identified problem of weak school leadership in order to improve the educational outcomes in schools. In this model, school principals of underperforming schools are paired up with business people with leadership experience for a period of one year to address the challenges facing their schools. The model includes a 12-month structured training programme which seeks to capacitate and support the paired principal and business leader in their partnership-building process. This study provides an in-depth investigation of the experiences of the partnerships and of the influence of the structured programme on these partnerships from the perspectives of the principals and of the business leaders. The effect of social differences on the partnerships was also considered. Among the theories used in this study are critical action learning and common ingroup identity. A qualitative research design was employed and data was collected from 10 school principals of “no fee” schools and from 12 business leaders. The results of the study reveal that the functionality of these partnerships is determined by their focus, which can be long-term and transformative or short-term and tending towards resolving the school’s immediate material needs. Further, these partnerships were found to be capable of improving school performance if the partners engaged in activities that promoted teaching and learning. Despite this potential, there was little monitoring of school performance. The results also indicate that the group-learning aspects included in the structured programme could encourage the partnership to focus on short-term goals which tend not to lead to long-term sustainable change in the school. The social tensions attributed to race and class divisions were found to have a minimal effect on the partnerships studied since the partners’ common vision, namely, to improve schools, allows them to maintain their unique identity either as principals or as business leaders. Because education reform is a complex and long-term project, the recommendations following this study point to the need for a more integrative approach in the PfP process, and a greater awareness of the need for a longer time scale in order to bring about the desired transformation in schools and consequently to South Africa’s education system.
A research project submitted in partial fulfilment of the requirements for Masters in Development Studies in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, March 2017.
Keywords: Educational leadership--South Africa; School management and organization--South Africa; Educational change--South Africa; School improvement programs--South Africa